Ethnoscience Study in Lambaleko Weaving in Tana Righu - Engge, Yohanes; Kerans, Geterudis; Malo, Meinfi Yanti (Vidya Karya, 2024)
Sumba Island has cultural characteristics that can be integrated into science learning, including Sumba woven cloth. The process of making Sumba weaving has cultural and scientific value. This research aims to determine the meaning and ethnoscientific value of making Lambaleko woven cloth. This study used qualitative research methods. This data was obtained through observation, interviews and documentation. The instruments used in this research were observation sheets, interview sheets, and documentation. The data analysis involves data reduction, data presentation, and concluding. The research results show that the tools and materials used in the weaving process are traditional tools and materials with varying classifications, showing the biodiversity level on the island of Sumba. Making Lambaleko weaving consists of eleven stages: a) preparing tools and materials such as Mbola, Bei tonnu, Koba, Malirra, Ghunna, Ghobola, Laketta, Bedo, Kalerre, Tent, Laka, Kalamaka, Ghobola ghunna, Ghobola zodo, Rande, Tukka, Kanagho, scissors and thread, b) tools starting to be assembled on the Mbola, c) unfurling the warp threads on the Bei tonnu, e) removing the weave from the Mbola, d) winding the threads on the Kanagho, f) straightening the threads on the woven fabric, g) installing the Rande, h) installing Tukka, i) installing Ghobola ghunna, Ghobola zodo, j) making motifs, and k) the process of making weaving until it becomes cloth. The weaving process is also related to physical material, frictional forces, pressure, gravitational forces, biological material, plant biodiversity, and chemical material, additives. In conclusion, Lambaleko woven cloth has ethnoscientific and cultural values that the community believes to be used in science learning related to biodiversity, friction, pressure, gravitational forces, and additives.